Faktor- Faktor Yang Mempengaruhi Kesiapsiagaan Perawat Dalam Menghadapi Bencana : literature Review - Eky Madyaning Nastiti (Fakultas Ilmu Kesehatan, 2022)
Disasters are a phenomenon that continues to experience an increase in incidence and has an impact on the number of deaths, injuries, infrastructure and economic damage. Nurses play an important role in the disaster preparedness stage. Purpose of this study: to analyze the factors that influence the preparedness of nurses in the face of disasters. Method: This literature review analyzes articles from 2010-2020 using two data bases: Google Scholar and Pubmed with the key words used: preparedness, disaster, nurse. Five articles were obtained which were analyzed according to JBI guidelines. Results: based on the results of the review, it shows that nurses' preparedness in facing disasters is influenced by several factors including: length of work, knowledge, self-efficacy, training in disaster simulation and availability of facilities and infrastructure. Conclusion: the availability of these five factors is beneficial for increasing the competence of nurses, especially in developing professional services in improving disaster preparedness.